​​The influence of maternal obesity on placental fatty acid composition, synthesis of inflammatory mediators and pregnancy outcomes - Wainwright, Esther (2024)
​Introduction: Obesity is a global issue with ever increasing prevalence, having detrimental effects on the health of the population. Maternal obesity has been identified to significantly increase the risk of prolonged and dysfunctional labour, labour induction and emergency caesarean delivery. An established rodent model of diet induced obesity has been utilised to unravel the potential mechanisms behind uncoordinated myometrial contractile function labour. In this model a high-fat, high-cholesterol (HFHC) diet successfully induces maternal obesity, significantly altering maternal fatty acid status leading to un-coordinated contractions that significantly prolongs labour. Potential mechanisms identified to be behind dysfunctional labour is a decrease in the uterine expression of key contractile associated proteins (CAPs), an increase in progesterone concentrations, the hormone that suppresses expression of the contractile proteins, and decreased circulating PGF2α that stimulates myometrial contractions during labour. ​ ​ Aims: The aim of this thesis was to first evaluate the impact the HFHC diet may have on the placenta in the maternal obesity model, focusing on its role in the initiation of labour. The second aim was to assess if the human placenta from obese women had the same characteristics. The third aim was to evaluate how these fatty acid profile changes may affect trophoblast cell's ability to produce pro-labour mediators, in vitro. Finally, the last chapter aimed to evaluate non-communicable disease and diet alongside obesity on pre-term birth, mode of delivery and birthweight, in a setting where obesity, NCDs and adverse pregnancy outcomes are extremely prevalent. Two of the most common NCDs associated with obesity and placental pathologies, hypertension and type 2 diabetes were evaluated alongside obesity, looking at how these effect pregnancy outcomes. The final prospective study aimed to evaluate any dietary patterns associated with pregnancy outcomes. ​ ​ ​Methods: Fatty acid profiles of the placental tissue from both the rat study and from human participants of different BMI were analysed through GCMS and RTqPCR to compare the fatty acid composition and gene expression profiles respectively. Gene expression profiles were centred around the placentas role in initiation of labour including hormone synthesis and signalling (e.g corticotrophin releasing hormone -CRH, Oestrogen receptor 1 -ER1 and cytochrome P450 family 17 subfamily A - CYP17), prostaglandin synthesis (e.g cyclooxygenase 2 - COX2), inflammatory regulators (e.g nuclear factor kappa B - NFκB and Sirtuin 1 SIRT1) and peroxisome proliferator-activated receptors - PPARs. HTR8-SVneo trophoblast cell line was treated with increasing doses of Oleic acid and pro-inflammatory cytokine interleukin 6 (IL-6) and prostaglandins PGE2 and PGF2a were measured using ELISA. Prostaglandin synthesis enzymes and PPARg mRNA levels were also investigated to attempt to elucidate a signalling pathway. Multinomial logistic regression was used to assess the joint impact of obesity and NCDs on mode of delivery, preterm birth and birthweight. A food frequency questionnaire was also used to assess dietary patterns and multinomial logistic regression used to understand the effects they may have on pregnancy outcomes. ​ ​ ​ Results: This experiment found significant alterations in the fatty acid composition of the placenta from obese pregnant rats and women. In the obese rat placentae, there was a significant decrease in saturated fatty acids, and an increase in monounsaturated fatty acids (MUFAs) as well as decreased desaturase enzyme activity. Similar results were found in placental tissue from obese pregnant women, although to a much lesser extent. Interestingly, only one of the genes quantified was differentially expressed. Placental expression of PPARg within the placenta was found to be significantly higher in HFHC fed rats but this was expressed any differently within the placenta of pregnant women of different BMI. In the cell culture study oleic acid at the highest physiological doses of (400µM) significantly decreased the synthesis of all the markers measured. Only one enzyme, responsible for producing PGE2 was found to decrease in a similar pattern with increasing oleic acid treatment. The retrospective cohort study found obesity to increase the risk of operative deliveries and remained significant after adjusting for confounding variables, for emergency CS. Once hypertension and type 2 diabetes were added into the model this no longer remained significant and neither of these had any significant effect on pregnancy outcomes looked at. No dietary patterns were significantly associated with any of these. ​ ​ Discussion: A diet high in saturated fats may create an anti-inflammatory response, seeing an increase in monounsaturated fatty acids, namely oleic acid within the placenta. The decrease in expression of genes associated with the prostaglandin biosynthetic pathway by high physiological levels of oleic acid may explain the reduced circulating PGF2a, and reduction in the expression of CAPs and dysfunctional contractions seen in the translational model. In conclusion the research findings from this thesis suggest further study into the effects of diet and fatty acid profiles as a risk factors or potential biomarkers for negative pregnancy outcomes are warranted.